Correlation between the static and dynamic responses of organic single-crystal field-effect transistors - Taiki Sawada (Nature Portfolio, 2020)
Though literature reports improvements in organic electronic device performance, understanding the correlation between static and dynamic device responses remains a challenge. Here, the authors correlate static and dynamic parameters in organic transistors by using the radiofrequency circuit model.